2016
DOI: 10.1002/jmri.25324
|View full text |Cite
|
Sign up to set email alerts
|

GABA quantitation using MEGA-PRESS: Regional and hemispheric differences

Abstract: Purpose To measure in vivo brain gamma-aminobutyric acid (GABA) concentrations, and assess regional and hemispheric differences, using MR spectroscopy (1H-MRS). Materials and Methods GABA concentrations were measured bilaterally in the frontal cortex (FC), parietal cortex (PC), and occipital cortex (OC) of 21 healthy young subjects (age range 20–29 years) using 3 Tesla Philips scanner. A univariate general linear model analysis was carried out to assess the effect of region and hemisphere as well as their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
0
33
3
Order By: Relevance
“…Discrepancy between our estimation and previous MEGA GABA measurements at 3 T are also seen in other brain regions. Frontal‐brain GABA was measured as 1.4 to 2.1 mM in previous studies at 3 T, which is higher than our estimate (0.87 mM). For PC, our estimate of 0.66 mM in a 7‐mL voxel is approximately 50% relative to a previous MEGA study in an 18‐mL voxel .…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Discrepancy between our estimation and previous MEGA GABA measurements at 3 T are also seen in other brain regions. Frontal‐brain GABA was measured as 1.4 to 2.1 mM in previous studies at 3 T, which is higher than our estimate (0.87 mM). For PC, our estimate of 0.66 mM in a 7‐mL voxel is approximately 50% relative to a previous MEGA study in an 18‐mL voxel .…”
Section: Discussioncontrasting
confidence: 91%
“…A recent study, which aimed to find regional differences of GABA at 3 T, reported 2.7 mM of GABA in the MO cortex. 30 Several other 3T studies using MEGA reported MO GABA/tCr of 0.15 to 0.2, 31-33 which corresponds to 1.2 to 1.6 mM when the tCr level is set to 8 mM. Discrepancy between our estimation and previous MEGA GABA measurements at 3 T are also seen in other brain regions.…”
Section: Discussion a Nd C Oncl Us I Oncontrasting
confidence: 66%
See 1 more Smart Citation
“…Recent advances in molecular MRI expand the capability of MRI even further. Molecular probes activated by an enzyme and localized by nanoparticles, molecular imaging biomarkers for metabolites of activated T cells for immunotherapy, hyperpolarized gas‐enhanced MRI, and quantitative analysis of MR spectroscopy of glutathione, gamma‐aminobutyric acid (GABA), glutamate, with high accuracy and reproducibility are just a few examples. MRI continues to contribute to the scientific discovery and understanding of many diseases that were never thought possible.…”
Section: Value Of Mr Through Research and Innovationmentioning
confidence: 99%
“…The low concentration of GABA and the presence of overlapping signals from more concentrated metabolites render GABA measurements ambiguous using conventional 1 H-MRS at 3.0 T (7). As a result, a spectral editing technique, MEscher-GArwood Point Resolved Spectroscopy (MEGA-PRESS (8)), is widely used to remove overlapping signals, allowing observations of GABA levels in healthy and diseased patients (911). …”
Section: Instructionmentioning
confidence: 99%